Analisis pemanfaatan e-learning madrasah: studi kasus di kabupaten Indramayu - Aziz Rizki Miftahul Ilmi; Masduki Duryat; Muh. Aripin Nurmantoro (Educatio, 2022)
E-learning madrasah is a learning media that aims to facilitate learning activities in order to get good learning outputs during the covid-19 pandemic. The results of a preliminary study conductedon all MTs Negeri in indramayu districts during covid-19 showed that there were still many teachers who had not yet utilized this learning media in the learning they have done and the output of learning outcomes had decreased. This decrease can be seen from the average repetition of 54 from the Minimum Completeness Criteria (MCC) which is set at 76. This study aims to explain the supporting and inhibiting factors experienced by students and teachers in learning science using madrasa e-learning during the covid-19 pandemic. The research method used in this study is a qualitative method with a case study type. This research was conducted on science learning at the madrasah tsanawiyah level in Indramayu districts. Respondents involved in this study were 458 class VIII students and five madrasah tsanawiyah teachers who were selected using two sampling techniques, namely cluster random sampling and purposive sampling. The supporting instruments in this study were observation sheets and interview sheets. Observation sheets were used to collect data related to the use of e-learning madrasah in science learning. Meanwhile, the interview sheets were used to obtain information about respondents' experiences in using e-learning madrasah and to digest information about the observed phenomena. The results showed that the use of e-learning madrasah in science learning had inhibiting and supporting factors including IT (Information and Technology) capabilities, adequate equipment, learning methods and modes, characteristics of teaching materials, network availability, parental support, and training on the use of e-learning madrasah for students. These seven things act as supporting factors and inhibiting factors that support the characteristics of each school.